Acquisition of Spanish nacinality and polygamic marriage: critical and practical aspects - Al Rached, Hani (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Nationality generates a political, legal and social link with the State that wants to apply for its nationality, and this requires that this link encompasses permanence in the land and integration into the customs and lifestyle of the country. Therefore, the request of the applicants for nationality in cases of polygamy will be denied, since they do not meet the requirement of “sufficient degree of integration into Spanish society”, required in art.22.4.CC. This paper tries to study the effectiveness of polygamous marriage as a reason for the denial of nationality, as pronounced by the ruling of the National Court of Madrid on February 4, 2019.